2018
DOI: 10.5897/ajar2017.12856
|View full text |Cite
|
Sign up to set email alerts
|

Litter production in a natural stand of Brazil nut trees (Bertholletia excelsa Bonpl.)

Abstract: This research estimated litter production and analyzed its relation to environmental variables such as maximum temperature, insolation, and rainfall. The study was conducted on a 300 × 300 m experiment as part of the project titled mapping of native Brazil nut stands and socio-environmental and economic characterization of Brazil nut production systems (MapCast), in the Tapajós National Forest (FLONA Tapajós). Every 30 days for one full year (August 2015 to July 2016), litterfall was collected and stored in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…So, our expectations were only partially met. A similar response of litterfall and leaf production to temperature and temperature increases in relation to historical records have been registered by Guerreiro et al (2018) in an Amazonian evergreen forest, who discussed these processes as an effect of abnormal or brusque changes in temperature after a long time of adaptation of tree species to low levels of variation in these factors. In restinga ecosystems, temperature variations can be even stronger due to low sandy soil specific heat.…”
Section: Effect Of Climatic Variability On Litterfallsupporting
confidence: 69%
See 1 more Smart Citation
“…So, our expectations were only partially met. A similar response of litterfall and leaf production to temperature and temperature increases in relation to historical records have been registered by Guerreiro et al (2018) in an Amazonian evergreen forest, who discussed these processes as an effect of abnormal or brusque changes in temperature after a long time of adaptation of tree species to low levels of variation in these factors. In restinga ecosystems, temperature variations can be even stronger due to low sandy soil specific heat.…”
Section: Effect Of Climatic Variability On Litterfallsupporting
confidence: 69%
“…Although it has been demonstrated that water availability is a major climate driver of litterfall production on annual basis across the tropics (Wagner et al 2016), many studies reported that litterfall is better explained by variations in temperature than in rainfall (Chave et al 2010, Ferreira et al 2014, Guerreiro et al 2018, Martinelli et al 2017. First, the relation between water availability and precipitation for plants is not straightforward and is determined by soil and plant characteristics, such as field capacity, root distribution, extractable water, etc (Wagner et al 2012).…”
Section: Effect Of Climatic Variability On Litterfallmentioning
confidence: 99%